Effects of reduced chemical application by mechanical-chemical synergistic weeding on maize growth and yield in East China - Fang, Huimin; Niu, Mengmeng; Wang, Xinzhong; Zhang, Qingyi (Frontiers in Plant Science, 2022)
There is growing concern about the environmental impact of chemicals and the long-term effects of mechanical weeding, which inhibits weed regrowth. Mechanical-chemical synergy has become an alternative weeding practice. In this paper, the effects of reduced chemical application by mechanical-chemical synergetic weeding on maize growth and yield are studied via synergistic weeding experiments. Experiments were carried out using three chemical reduction ratios (25%, 50%, and 75%) and two chemical applications (full width and only seeding row). The existing inter- and intra-implements were integrated as weeding machinery for full range mechanical weeding. Two indicators (leaf area and dry matter weight) were defined as growth characteristics at the filling and maturity stages. The results show that the leaf area of mechanical-chemical synergistic treatments was larger than those of single mechanical or chemical weeding treatments at the filling stage, but there was no significant difference between the leaf area values of the synergetic treatments (P=0.939). At the filling and maturity stages, the dry matter weight of mechanical-chemical weeding treatments was greater compared to the chemical weeding treatment. At the filling stage, the dry matter weight of the mechanical-chemical synergistic weeding treatments was less than that of the mechanical weeding treatment. In contrast, at the maturity stage, the dry matter weight of mechanical-chemical weeding treatments was greater, indicating that the promotional effect of the mechanical-chemical synergistic model was more pronounced at the later stage of crop growth. Single weeding or non-weeding treatment significantly affected the number of grains per ear (p=0.037) and 1000 grain weight (p=0.019), but it has been observed to have no significant effect on yield (p=0.504). The number of grains per ear, 1000 grain weight, and yield of the mechanical-chemical synergistic treatment were observed to be better than those of the chemical treatment. When compared with the full range of mechanical weeding treatments, only synergistic treatment produced a higher yield. From the perspectives of leaf area and dry matter, yield and its components, at the filling and maturity stage, the effect of mechanical-chemical synergy with 50% chemical reduction is the best recommendation as it reduces the dosage of chemical application, without significantly affecting crop growth and yield.